Hydrodynamic investigation on gas–solid two‐phase flow character in a circulating fluidized bed. Issue 4 (17th December 2013) - Wang, Xueyao; Fan, Baoguo; Lei, Jing; Lei, Fulin; Xiao, Yunhan
ABSTRACT Riser is the key component of circulating fluidized bed reactors, in which gas–solid or catalytic reactions occurs. The flow hydrodynamics and Geldart B type solids' concentration profiles in the riser, under higher superficial gas velocity, larger solids circulation rate, and wide ranges of operating conditions, were the focuses of this experimental study. The typical core‐annulus structure with clusters and a small amount of particles' back‐mixing phenomena near the wall of the riser was observed. The axial solids concentration distributions in the riser with an abrupt T‐shape exit were characterized by a dense region near the bottom, a dilute region toward the up‐middle zone, and a dense region near the top exit. Solids became dilute, and the back‐mixing phenomena weakened with the increase of superficial gas velocity. And the solids concentration at the same height position increased with the increment of solids circulation rate. Furthermore, the effects of two exit configurations, namely smooth C‐shape and abrupt T‐shape, on the flow characteristics were investigated. In order to compare the influence of particles' density and diameter, four single Geldart D particles and a soybean and millet two‐phase mixture are chosen as bed materials to study the bubbling bed flow character. Copyright © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.